A concise review of magnetic resonance molecular imaging of tumor angiogenesis by targeting integrin αvβ3 with magnetic probes - Liu Y (Dove Medical Press, 2013)
Yajie Liu, Yi Yang, Chunfu Zhang School of Biomedical Engineering and Med-X Research Institute, Shanghai Jiao Tong University, Shanghai, People’s Republic of China Abstract: Angiogenesis is an essential step for the growth and spread of malignant tumors. Accurate detection and quantification of tumor angiogenesis is important for early diagnosis of cancers as well as post therapy assessment of antiangiogenic drugs. The cell adhesion molecule integrin αvβ3 is a specific marker of angiogenesis, which is highly expressed on activated and proliferating endothelial cells, but generally not on quiescent endothelial cells. Therefore, in recent years, many different approaches have been developed for imaging αvβ3 expression, for the detection and characterization of tumor angiogenesis. The present review provides an overview of the current status of magnetic resonance molecular imaging of integrin αvβ3, including the new development of high sensitive contrast agents and strategies for improving the specificity of targeting probes and the biological effects of imaging probes on avB3 positive cells. Keywords: integrin αvβ3, molecular imaging, MRI, paramagnetic liposome, superparamagnetic iron oxide particles, tumor angiogenesis